The Effect of E-Service Quality and Brand Image on Customer Loyalty with Customer Satisfaction as a Mediation Variable - Ilham Firmansyah; Mahfudz Mahfudz (Journal of Business Social and Technology, 2023)
This research takes the object of study on Tiktok Shop, which is an e-commerce platform that has advantages compared to its rivals, namely being able to combine social media activities with e-commerce. This study aims to analyze and test the effect of e-service quality and brand image on customer satisfaction and customer loyalty among TiktokShop users. In this study, the researchers used a purposive sampling method using a manual questionnaire and also a Google form, and obtained 110 respondents who live in Semarang City and have also used the Tiktok Shop feature for shopping. The data analysis method used in this study is structural equation modeling using AMOS software. The results of direct testing between E-Service Quality and E-Customer Satisfaction show that there is a significant and positive effect. The results of direct testing between Brand Image and E-Customer Satisfaction show that there is a significant and positive effect. The results of direct testing between E-Service Quality and E-Customer Loyalty show that there is a significant and positive effect. The results of direct testing between Brand Image and E-Customer Loyalty show that there is a significant and positive effect. The results of direct testing between E-Customer Satisfaction and E-Customer Loyalty show that there is a significant and positive effect. The results of direct testing between Brand Image and E-Customer Loyalty show that there is a significant and positive effect. The results of direct testing between E-Customer Satisfaction and E-Customer Loyalty show that there is a significant and positive effect. The results of direct testing between Brand Image and E-Customer Loyalty show that there is a significant and positive effect. The results of direct testing between E-Customer Satisfaction and E-Customer Loyalty show that there is a significant and positive effect